Reanimating Chicago: Review of Dave Aftandilian and Gavin Van Horn, eds. City Creatures: Animal Encounters in the Chicago Wilderness - Mershon, Katharine (Humanimalia, 2016)
Dave Aftandilian, and Gavin Van Horn, eds. City Creatures: Animal Encounters in the Chicago Wilderness. Chicago and London: The University of Chicago Press, 2015. xi+377 pp. 30.00 hb; 18.00 e-book.